Identification of Intermediate and Branch Metabolites Resulting from Biotransformation of 2-Benzoxazolinone by Fusarium verticillioides - Glenn, A. E. (American Society for Microbiology, 2003)
Detoxification of the maize (Zea mays) antimicrobial compound 2-benzoxazolinone by the fungal endophyte Fusarium verticillioides involves two genetic loci, FDB1 and FDB2, and results in the formation of N-(2-hydroxyphenyl)malonamic acid. Intermediate and branch metabolites were previously suggested to be part of the biotransformation pathway. Evidence is presented here in support of 2-aminophenol as the intermediate metabolite and 2-acetamidophenol as the branch metabolite, which was previously designated as BOA-X. Overall, 2-benzoxazolinone metabolism involves hydrolysis (FDB1) to produce 2-aminophenol, which is then modified (FDB2) by addition of a malonyl group to produce N-(2-hydroxyphenyl)malonamic acid. If the modification is prevented due to genetic mutation (fbd2), then 2-acetamidophenol may accumulate as a result of addition of an acetyl group to 2-aminophenol. This study resolves the overall chemistry of the 2-benzoxazolinone detoxification pathway, and we hypothesize that biotransformation of the related antimicrobial 6-methoxy-2-benzoxazolinone to produce N-(2-hydroxy-4-methoxyphenyl)malonamic acid also occurs via the same enzymatic modifications. Detoxification of these antimicrobials by F. verticillioides apparently is not a major virulence factor but may enhance the ecological fitness of the fungus during colonization of maize stubble and field debris.